Use of Military Vocabulary as a Manipulation Tool During the Pandemic - BIDERKESEN, DURDU; AGEEVA, JULIYA VICTOROVNA; ÜÇGÜL3, SEVINÇ (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article considers military vocabulary as one of the effective language tools with which the manipulation of the readers' consciousness in the media is carried out. We concluded that the use of military vocabulary in a manipulative function is not prohibited, but the internal principles of journalists should tell them whether a military word is really necessary or it is simply a tool of speculation by the feelings of the readers. At the same time, readers, who are aware of the rich manipulative potential of military vocabulary, should strive to resist the manipulations created with its help.RESUMEN El artículo considera el vocabulario militar como una de las herramientas lingüísticas efectivas con las que se lleva a cabo la manipulación de la conciencia de los lectores en los medios. Llegamos a la conclusión de que el uso del vocabulario militar en una función de manipulación no está prohibido, pero los principios internos de los periodistas deberían decirles si una palabra militar es realmente necesaria o si es simplemente una herramienta de especulación por los sentimientos de los lectores. Al mismo tiempo, los lectores, que son conscientes del rico potencial de manipulación del vocabulario militar, deben esforzarse por resistir las manipulaciones creadas con su ayuda.